Mapping The Futures Of Malaysian Higher Education:A Meta –Analysis Of Futures Studies In The Malaysian Higher Education Scenario - Ithnin, Fazidah; Sahib, Shahrin; Chong, Kuan Eng; Sidek, Safiah; Raja Harun, Raja Nor Safinas (Tamkang University, 2018)
Futures studies are not new to the Malaysian Higher Education scenario. Numerous research articles have been written documenting details of futures interventions ranging from intensive silo university-based programmes to the centralized ministry-based ones. Universities such as Universiti Sains Malaysia and Universiti Teknikal Malaysia Melaka manifested the relevance of futures-oriented thinking and planning among its stakeholders, which led to intensive futures workshop held in the early years of 2002 and 2012 respectively. The Ministry of Higher Education through its Higher Education Leadership Academy or AKEPT had also initiated structured futures programmes in the years of 2012-2014 for higher education stakeholders consisted of vice-chancellors,deputy vice-chancellors, university professors and academics.Although many studies have been shared with reference to the futures studies efforts by Malaysian universities and the ministry, but a comprehensive meta-analysis has not been made available yet. This study is a meta-analysis based on futures scenarios articles produced by experts and practitioners of foresight studies. It provides a run-through of the foresight endeavours with reference to the Malaysian Higher Education specifying details on the conceptual framework adopted, methods, results and discussions with a strong indication of the unequivocal importance of futures studies in canvassing a dynamic image of the preferred future; subsequently triggering deeper futures thinking and innovation- oriented higher education community.